The Knowledge and Attitude of The Fishermen of Ujong Blang About the First Aid of Drowning Victims - Rizka, Adi; Millizia, Anna; Moulidiya, Elvina (Fakultas Kedokteran Universitas Malikussaleh, 2023)
Drowning is a respiratory disorder due to being submerged in liquid, this condition can cause loss of life if the victim is not immediately given help. First aid in drowning victims is essential to avoid disability and death. Currently, public knowledge of the first handling of drowning victims is still low. Therefore, health counseling is one way that can be done to improve public knowledge and attitudes in providing first aid to drowning victims. This study aims to determine the effect of counseling on the initial handling of drowning victims at sea on the knowledge and attitudes of fishermen in Ujong Blang Village, Lhokseumawe City, Aceh Province, Indonesia. This study involved 75 fishermen from Ujong Blang village as respondents. Respondent is taken by purposive random sampling technique. Measurement of knowledge and attitudes is carried out before and after counseling. The results of this study showed that the majority of respondents before being given education had an average knowledge of the good category of 40%, then increased to 92% after being given counseling. The attitude of respondents before being given counseling was the majority in the good category as much as 66.7%, then increased after being given counseling to 89.3%. The results of statistical analysis obtained p value <0.05, it was concluded that there was an influence of health counseling on the first handling of seawater drowning victims on the knowledge and attitudes of fishermen in Ujong Blang village, where respondents' knowledge and attitudes increased after counseling.